The Influence of Internal Control Systems, Human Resource Competence and Work Motivation on the Quality of Financial Reports (Study of Regional Apparatus Organizations in the City of Palu) - Ahmad Rusdiaman; Jurana; Femilia Zahra; Sugianto (Pustaka Digital Indonesia, 2026)
This study aims to examine and analyze the partial and simultaneous effects of internal control systems, human resource competence, and work motivation on the quality of financial statements in Regional Apparatus Organizations (OPD) of Palu City. This research employs a quantitative approach using primary data collected through structured questionnaires distributed to 82 respondents from 41 OPDs. The sampling technique used is a saturated sampling method. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25.0. The results indicate that internal control systems, human resource competence, and work motivation have a positive and significant effect on the quality of financial statements, both simultaneously and partially. Human resource competence shows the most dominant influence compared to other variables. These findings suggest that improving the effectiveness of internal control systems, enhancing employee competencies, and strengthening work motivation are essential factors in producing reliable, relevant, and high-quality financial reports in the public sector. This study contributes to the public sector accounting literature by providing empirical evidence on the determinants of financial reporting quality at the local government level. Practically, the findings offer insights for policymakers to strengthen governance, accountability, and transparency in financial management.